2016
DOI: 10.1021/jacs.6b06467
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Regulation of the Rotational Speed in a Light-Driven Molecular Motor

Abstract: The rotational speed of an overcrowded alkene-based molecular rotary motor, having an integrated 4,5-diazafluorenyl coordination motif, can be regulated allosterically via the binding of metal ions. DFT calculations have been used to predict the relative speed of rotation of three different (i.e., zinc, palladium, and platinum) metal dichloride complexes. The photochemical and thermal isomerization behavior of these complexes has been studied in detail using UV–vis and 1H NMR spectroscopy. Our results confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 65 publications
0
80
0
Order By: Relevance
“…[21,26] Since it was immediately recognized that the rate-limiting steps of the rotary cycles of 1 and other overcrowded alkenes are primarily the thermal steps, much experimental work was in the subsequent years and continuously up until today devoted to accelerating these particular steps. [25][26][27][28][50][51][52][53][54][55][56] Encouragingly, this work produced many powerful secondgeneration overcrowded alkenes. [25,27,28] Paralleling the experimental efforts, a series of systematic quantum chemical studies revealed a number of ways to further lower the thermal free-energy barriers of the second-generation motors, [57][58][59] that we now turn to discussing.…”
Section: Overcrowded-alkene Motorsmentioning
confidence: 96%
See 1 more Smart Citation
“…[21,26] Since it was immediately recognized that the rate-limiting steps of the rotary cycles of 1 and other overcrowded alkenes are primarily the thermal steps, much experimental work was in the subsequent years and continuously up until today devoted to accelerating these particular steps. [25][26][27][28][50][51][52][53][54][55][56] Encouragingly, this work produced many powerful secondgeneration overcrowded alkenes. [25,27,28] Paralleling the experimental efforts, a series of systematic quantum chemical studies revealed a number of ways to further lower the thermal free-energy barriers of the second-generation motors, [57][58][59] that we now turn to discussing.…”
Section: Overcrowded-alkene Motorsmentioning
confidence: 96%
“…While many experimental and computational efforts have been made to improve the thermal isomerization performance of overcrowded-alkene motors, [25][26][27][28][50][51][52][53][54][55][56][57][58][59] it is also important to explore ways to control and modulate their photochemical steps [67][68][69] or the possibility to design new classes of rotary motors whose photochemical steps proceed more efficiently. Through NAMD simulations, [49] it has been inferred that the photoisomerization QYs of overcrowded alkenes are limited (to 0.2-0.3 [68,73] ) by the requirement that the torsional motion around the central olefinic bond in the photoactive first excited singlet state (S 1 ) is coupled to a substantial pyramidalization of one of the carbon atoms, or else the conical intersection (CI) seam with the ground state (S 0 ) cannot be reached.…”
Section: And (P)-unstable-e Species Formed By Photoisomerizations Of mentioning
confidence: 99%
“…[1][2][3] Fundamental developments have discovered fascinating phenomena and enabled a wealth of applications in the gas phase, [4][5][6][7][8] in solution, 4,[9][10][11] in crystals, 4,12 on surfaces, [4][5][6][13][14][15] and in biosystems. 16 Here we use a molecular model rotor to demonstrate the way from molecular quantum dynamics to explicitly time dependent statistical thermodynamics.…”
mentioning
confidence: 99%
“…+ with inner triangular wheel rotating in outer pseudo-rotating bearing (schematic). Clockwise and anti-clockwise tunneling from the global minimum GM 16 to the neighbors GM 15 and GM 17 , respectively (left), and then sequentially to GM 14 , GM 13 , GM 12 , GM 11 , etc, and simultaneously also to GM 18 , GM 19 , GM 20 , GM 21 , etc (right). Subsequent tunneling tends to populate all GMs, see Fig.…”
mentioning
confidence: 99%
“…A major experimental effort has therefore been invested to improve the rates and efficiencies of overcrowded alkene-based molecular motors. 9,10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In this regard, computational methods are particularly useful as they can provide detailed insights into the mechanisms and dynamics of the chemical reactions that produce the rotary motion. Such insights may not be easily obtained by experimental techniques, because of the difficulties associated with detecting transient species such as reactive intermediates and transition structures (TSs) or measuring the timescales of ultrafast processes.…”
Section: Introductionmentioning
confidence: 99%